ESTIMATION OF RETURN LEVELS AGAINST DIFFERENT RETURN PERIODS OF EXTREME ANNUAL RAINFALL OVER BALUCHISTAN - Ali, M.; Jan, B.; Iqbal, M. J. (The Nucleus, 2012)
Unprecedented heavy monsoon rainfall began in the last week of July 2010 in the Northern part of our country, causes floods in Baluchistan and Sindh. As the high frequency rainfall events are a significant cause of current severe flooding in Pakistan and any fluctuation in the level of such events may cause huge economic losses as well as social problem, urban structures (i.e. dams, urban drainage systems and flood). Statistical distributions are used to identify extremes of annual rainfall of different cities of Baluchistan (Quetta, Sibbi, Khuzdar, Lasbella, Dalbandin and Pasni) with their return periods. Analysis predicts that Gumbel Max.(GM) Distribution is the best fitted distribution for Sibbi and Lasbella while the GEV distribution is the best fitted for Quetta, Khuzdar, Dalbandin and Pasni. The analysis also suggests that different cities of Baluchistan have 30-years return period for getting more than 90 mm average daily rainfall while they have 100-years return period for receiving more than 118 mm daily rainfall. This suggests for suitable flood forecasting and improving the river structure in Baluchistan, Pakistan.